"I can put the medicine in his soup, Doctor!". Issue 5 (29th April 2005) - Wong, J G W S; Poon, Y; Hui, E C
Abstract : The practice of covertly administering medication is controversial. Although condemned by some as overly paternalistic, others have suggested that it may be acceptable if patients have permanent mental incapacity and refuse needed treatment. Ethical, legal, and clinical considerations become more complex when the mental incapacity is temporary and when the medication actually serves to restore autonomy. We discuss these issues in the context of a young man with schizophrenia. His mother had been giving him antipsychotic medication covertly in his soup. Should the doctor continue to provide a prescription, thus allowing this to continue? We discuss this case based on the "four principles" ethical framework, addressing the conflict between autonomy and beneficence/non-maleficence, the role of antipsychotics as an autonomy restoring agent, truth telling and the balance between individual versus family autonomy.